Análise da gestão da pequena propriedade rural: o caso dos produtores de leite da região do grande Santa Rosa - RS - Pudell, Valmir (2006)
The referred work has as an objective to propose actions that aggregate value to small rural properties of the sector of milk in the region of Santa Rosa in the State of Rio Grande do Sul, for productivity and profitability increase of these properties. Thus, it searched to identify and analyze the present situation in what the small milk producers of the region are, regarding to management and production practices. It was done visits and interviews in coops, syndicates of rural producers, IBGE and other entities associated the sector, aiming to search information about milk activity. It was also interviewed the small producers of milk , where it could be verified that almost does not exist any practice of formal management developed by them, the way that, the management is totally informal based in the empirical knowledge passed through generation to generation. Based in this diagnostic it was developed a proposal for the criation of a management system, where in a decentralized and cooperative way several entities like city halls, coops, syndicates of rural producers, EMATER and niversities from the region should interact among themselves and with the producers aiming the formulation of policies of development and planning for the implementation of new technologies and management techniques for the production increase aiming the family sustentation and the development of the region.